2006
DOI: 10.1007/s00464-005-0406-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in postoperative pain after laparoscopic cholecystectomy

Abstract: Early postoperative pain after LC was more severe in female patients, and patients with high VAS scores tended to use analgesics more frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
7
32
0
5
Order By: Relevance
“…It has been described that females have lower pain threshold and tolerance; however it is questioned if this could be due to better females' verbalization and to differences in female endogenous opioid system, which might have lower sensitivity as compared to males and supports our results where 28.57% of females referred postoperative pain as compared to 18.92% of males 5 . Females also refer more severe pain, as found by a different study 7 . The correlation between age and postoperative pain is shown by the literature as inversely proportional 8 , which differs from our findings where the upper age extreme has referred more pain as compared to mean age (40 years).…”
Section: Discussionmentioning
confidence: 79%
“…It has been described that females have lower pain threshold and tolerance; however it is questioned if this could be due to better females' verbalization and to differences in female endogenous opioid system, which might have lower sensitivity as compared to males and supports our results where 28.57% of females referred postoperative pain as compared to 18.92% of males 5 . Females also refer more severe pain, as found by a different study 7 . The correlation between age and postoperative pain is shown by the literature as inversely proportional 8 , which differs from our findings where the upper age extreme has referred more pain as compared to mean age (40 years).…”
Section: Discussionmentioning
confidence: 79%
“…With regard to drugs used, patients receiving opioids had lower prevalence of pain (57%) as compared to those not receiving opioids (63%). However, this correlation was not statistically significant, which may be associated to the fact that different surgical procedures with different nociceptive stimulations were evaluated 18 . In addition, every patient has a different sensitivity to pain and may report different pain intensities for a same procedure 21 .…”
mentioning
confidence: 78%
“…The prevalence of postoperative pain varies widely 18 . Studies have shown that up to 90% of patients submitted to surgical procedures have some type of pain in the first 24 postoperative hours and, if intensity is considered, 40 to 60% of patients report moderate to severe pain 1,2 .…”
Section: Discussionmentioning
confidence: 99%
“…A influência do sexo do paciente na DPO é também destacada em outros estudos (12,16,23,24) , em que normalmente se evidenciam uma maior prevalência para o sexo feminino, mas sob um único tipo de cirurgia e tendo em conta a possibilidade das mulheres verbalizarem a dor com mais facilidade e alegarem com mais facilidade a dor severa (2,16,24) . No presente estudo, houve associações significativas entre o sexo e local ou intensidade da dor, mas não com a prevalência.…”
Section: Discussionunclassified
“…Os pacientes entrevistados e avaliados quanto à analgesia pós-operatória responderam a um questionário individual, semiestruturado (elaborado pelos pesquisadores) e baseado em variáveis de interesse, conforme reportado na literatura (2,11,12,22,23) . Aplicado em local reservado, por um único pesquisador e em voz alta, objetivando-se evitar interpretações errôneas.…”
Section: Métodosunclassified